(untitled) (Journal of Pedagogical Inventions and Practices, 2023)
In this article, two vital requirements of the new and innovative educational era: language learning and simultaneously further development of critical thinking skills processes integration issues are highlighted. Basically, it is intended to theoretically and practically test whether the method of analyzing detective short stories using the "Six Thinking Hats" method in reading classes can develop students’ critical thinking skills and increase their potential to learn a second language effectively.